Grounded theory and succession in family businesses: an overview and some directions - Feuser, Noellen Silva Amorim; Binotto, Erlaine; Gonçalves, Lidiane Parron; Cremon, Thais (Revista de Administração da UFSM, 2025)
Purpose: The study aimed to analyze research on succession in family businesses that applied Grounded Theory (GT) method and propose a research agenda. Methodology: A systematic literature review was conducted using Scopus and Web of Science databases. Data analysis was carried out using two distinct approaches: the first explored the conceptual and theoretical aspects of the studies, while the second focused on the application of the GT method. Findings: The analyzed studies examined succession from different perspectives, identifying four thematic clusters: Family Businesses, Successors, Family, and Grounded Theory. This research explored succession stages and processes, successor development and leadership, family roles and influence, as well as intergenerational communication, conflicts, and decision-making. Based on these clusters, a research agenda was developed that offers insights into the field of family business succession through the application of the GT method. Despite the extensive literature, studies that generate theories or strictly adhere to the fundamental principles of GT remain scarce. Research implications: This study highlights research opportunities through the application of the GT method, contributing to a deeper understanding of the succession process in family businesses and the formulation of sustainable business policies. Originality: This study outlines pathways for future research in this field based on the four identified thematic groups, addressing research gaps, providing insights, and fostering continued investigations to support the development of family businesses.